AFGANİSTAN (1945-1989) - ŞENLİ, BURHANETTİN (Fırat Üniveristesi, 2017)
Bu doktora tezi, İkinci Dünya savaşından yani 1945 yılında sonra başlayan soğuk savaş dönemi ile bu dönemin sonu ve SSCB'nin dağılmasının başladığı kabul edilen 1989 yılında Rus işgalinin bittiği dönemde Afganistan tarihini incelemeyi amaçlamaktadır. Öncelikle Afganistan'ın tarihi ve coğrafi yapısı incelenmiştir. Daha sonra Afganistan'ın Jeopolitik yapısı ele alınmış ve Türkiye Cumhuriyeti ile yakın tarihlere rastlayan kuruluşu anlatılmıştır. Özellikle Atatürk döneminde Afganistan-Türkiye Cumhuriyeti ilişkilerine kısaca değinilmiştir. Afganistan'daki siyasi hareketler ile Afganistan'ın Sovyetlere yaklaşması geniş bir şekilde incelenmiş, bilahare Rus işgali ile geri çekilmesi yine geniş bir araştırma sonucu Rus ve Doğu Bloku ülkelerinin arşiv kaynaklarına ve diğer kaynaklara dayanarak incelenmiştir. Daha sonra Rus işgaline karşı büyük güçlerin tepkisi ve ABD'nin işgale verdiği destek ile mülteciler sorunu ele alınmıştır. Bu arada Afganistan'ın idari ekonomik kültürel ve dini yapısı kısaca incelenmiştir. Son bölümde Afganistan'ın dış politikası, komşuları ve Türkiye Cumhuriyeti olan ilişkileri ortaya konmuştur. İncelemede elde edilen veriler sonuç bölümünde açıklanarak ortaya konmuştur. Anahtar Kelimeler: Afganistan, Sovyet İşgali, Rus İşgali

This doctoral thesis (Ph. D. Dissertation) aims to examine the history of Afghanistan during the period of the Cold War, which began after the Second World War in 1945, and the end of that period and the Russian occupation in 1989, when the dissolution of the USSR began. First of all, the history and geographical structure of Afghanistan has been examined. Later on, the geopolitical structure of Afghanistan was discussed and the institution that coincided with the recent history of the Republic of Turkey was explained. Especially during the Ataturk period, relations of Afghanistan and Turkish Republic were briefly mentioned. The political movements in Afghanistan and the approach of Afghanistan to the Soviets have been extensively studied and the withdrawal by the Russian invasion has been examined again based on archival sources of Russian and Eastern Bloc countries and other sources. Later on, the reaction of the great powers against the Russian occupation and the support given by the US to the occupation, and the problem of refugees were addressed. In the meantime, the administrative, economic, cultural and religious structure of Afghanistan has been briefly examined. In the last part, the foreign policy of Afghanistan, its relations with its neighbors and relations with the Republic of Turkey have been revealed. The data obtained in the review are explained in the conclusion section. Key Words: Afghanistan, Soviet Invasion of Afghanistan, Russian Invasion of Afghanistan
Afghanistan (1945-1989)
Keywords: Tarih; Uluslararası İlişkiler